The Influence of Organizational Behavior in Political Decision Making in Student Organizations - Karmelia, Arina; Saepudin, Eli Apud; Revita, Natasya; Khurotul Ain, Intan; Tamimi, Muhammad; Ardiansyah, Adi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Student institutions or student organizations (ormawa) are containers for implementing student activities on campus. Student organizations are one of the most important elements in the educational process in higher education. The existence of ormawa is a vehicle and means of student self-development towards broadening horizons, increasing scholarship, personality integrity, instilling a scientific attitude, and understanding of the direction of the profession and at the same time increasing cooperation and fostering a sense of unity and integrity. One of them is in behaving in an organization that allows you to make decisions in politics. In providing students with skills so that students are able and ready to meet the needs of the world of work and in society. In addition to providing knowledge, skills, universities must also provide character values or soft skills so that in the end these students have a sense of sensitivity in their social interactions, both in their social interactions with the community, and in the field of work they do. Partnerships (kempus) can be an effective training ground for shaping students'' democratic attitudes. Partnerships can be made between student organizations and other parties such as universities, student organizations, and the private sector. Organizational Behavior is a discipline that studies how individual-level, group-level behavior should be, and its impact on performance (both individual, group, and organizational performance). In common with all social sciences, organizational behavior seeks to control, predict, and explain. However, there is some controversy over the ethical impact of focusing on worker behavior. Because of this, organizational behavior (and its adjacent study, industrial psychology) is sometimes accused of being a scientific tool of the powerful. Despite these accusations, Organizational Behavior can play an important role in organizational development and work success. Decision-making, on the other hand, is the act of selecting alternatives. It is related to management functions. For example, when managers plan, manage, control, they make decisions. However, classical theorists did not explain these decisions in general terms.